1998
DOI: 10.1016/s0969-2126(98)00021-5
|View full text |Cite
|
Sign up to set email alerts
|

The allosteric regulation of pyruvate kinase by fructose-1,6-bisphosphate

Abstract: The structure and location of the allosteric activator site agrees with the pattern of alternate genetic splicing of the PK gene in multicellular eukaryotes that distinguishes between a non-regulated isozyme and the regulated fetal isozymes. The conformational differences observed between the active sites of inactive and fully active PK enzymes is in agreement with the recently determined thermodynamic mechanism of allosteric activation through a 'metal relay' that increases the affinity of the enzyme for its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
411
0
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(437 citation statements)
references
References 61 publications
21
411
0
5
Order By: Relevance
“…The highly conserved Ala154 is located close to active site residues Arg116 (involved in substrate binding [Valentini et al, 2002] and ATP/ADP binding [Larsen et al, 1994;Muirhead et al, 1986;Rigden et al, 1999]) and Asp156 (involved in K 1 binding [Jurica et al, 1998;Larsen et al, 1994;Rigden et al, 1999;Wooll et al, 2001]). The approximate 50% decrease in PK enzymatic activity as measured in the heterozygous Patient 24 indicates that substitution with threonine may perturb this interaction, thereby hampering catalysis.…”
Section: The Novel Pgly111arg Pk Variant Is Prevalent In the Dutch Pmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly conserved Ala154 is located close to active site residues Arg116 (involved in substrate binding [Valentini et al, 2002] and ATP/ADP binding [Larsen et al, 1994;Muirhead et al, 1986;Rigden et al, 1999]) and Asp156 (involved in K 1 binding [Jurica et al, 1998;Larsen et al, 1994;Rigden et al, 1999;Wooll et al, 2001]). The approximate 50% decrease in PK enzymatic activity as measured in the heterozygous Patient 24 indicates that substitution with threonine may perturb this interaction, thereby hampering catalysis.…”
Section: The Novel Pgly111arg Pk Variant Is Prevalent In the Dutch Pmentioning
confidence: 99%
“…The C domain contains the binding site for FBP. Subunit interactions at the interfaces between the A domains (A/A 0 subunit interface) and the C domains (C/C 0 subunit interface), as well as A/B and A/C interdomain interactions within one subunit are considered to be key determinants of the allosteric response, which involves switching of the PK tetramer from the low-affinity T-state to the high-affinity R-state [Fenton and Blair, 2002;Jurica et al, 1998;Mattevi et al, 1995;Rigden et al, 1999;Valentini et al, 2000Valentini et al, , 2002Wooll et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…They are expressed, respectively, in specific tissues. The M2 isoform, a splice variant of M1 is expressed during embryonic development (11) and tumor formation. It has been reported that tumor cells exclusively express PKM2 (10,12).…”
Section: Introductionmentioning
confidence: 99%
“…Most of them exist as tetramers of identical subunits (Kayne, 1973;Schramm et al, 2000;Fothergill et al, 2000). The crystal structures of cat, rabbit muscle, yeast, Escherichia coli and Leishmania mexicana PKs have been reported and their overall structures are similar (Stuart et al, 1979;Larsen et al, 1994;Jurica et al, 1998;Speranza et al, 1989;Rigden et al, 1999). PKs from the genus Bacillus and some other bacteria have a long extra C-terminal sequence (ECTS) composed of about 110 amino-acid residues (Sakai & Ohta, 1993;Tanaka et al, 1995;Kaneko et al, 1996;Muñ oz et al, 1997Muñ oz et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%